ISLAMISASI ILMU PENGETAHUAN - Syafrizal, Syafrizal; Aliasar, Aliasar; Aprison, Wedra (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this discussion is the Origin and Characteristics of Madrasas. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. The research results show that Al-Faruqi was the first person to initiate the Islamization of science. His intellectual sharpness and scientific criticism brought him to the conclusion that western-style social sciences show quite basic methodological weaknesses, especially when applied to understanding the reality of social life of Muslims who have a very different outlook on life from Western society. In carrying out the process of Islamization of knowledge, there are several objectives, namely: Mastering modern scientific disciplines, Mastering Islamic heritage, establishing special relevance to every field of modern science, Finding ways for creative synthesis between (Islamic) heritage and modern science, Building Islamic thought in the path that leads to obedience to God’s law, there is recognition of the existence of a hierarchy or levels of knowledge, Laying revelation the highest standard in discovering the truth.